Reduksi Semen Dengan Fly Ash Dengan Bahan Tambah Polycarboxilate Terhadap Kuat Tekan Dan Kuat Tarik Beton - Sammin, Widianto; Syahriman, Syahrul; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The structural engineering field is advancing rapidly. Fly Ash contains silica, similar to cement. This study examines the use of Fly Ash waste as a cement substitute in concrete production, with polycarboxylate added. Fly Ash was used at 15% and 30% with polycarboxylate at 1% and 2%. The target compressive strength was 25 MPa, with normal concrete mix. Tests focused on compressive strength in polycarboxylate variations. Another set of concrete mixes substituted 15% and 30% cement with Fly Ash, adding polycarboxylate at 1% and 2% of cement content. Results showed a compressive strength of 25.38 MPa for normal concrete and 25.78 MPa and 25.94 MPa for 1% and 2% polycarboxylate mixes, respectively. With 15% and 30% Fly Ash plus 1% polycarboxylate, compressive strength increased by an average of 0.635 MPa; with 2% polycarboxylate, it averaged 5.25 MPa. Similarly, for tensile strength, 1% polycarboxylate with 15% and 30% Fly Ash achieved an average of 5.45 MPa, while 2% polycarboxylate reached 18.63 MPa with the same Fly Ash percentages.